2019
DOI: 10.1101/587444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yellow Fever Vaccine Protects Resistant and Susceptible Mice Against Zika Virus Infection

Abstract: Zika virus (ZIKV) emerged as an important infectious disease agent in Brazil in 2016. Infection usually leads to mild symptoms but severe congenital neurological disorders and Guillain-Barré syndrome have been reported following ZIKV exposure. The development of an effective vaccine against Zika virus is a public health priority, encouraging the preclinical and clinical studies of different vaccine strategies. Here, we describe the protective effect of an already licensed attenuated yellow fever vaccine (17DD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Taken together, these studies suggest that the yellow fever vaccine may be important in the prophylaxis of ZIKV infections and their outcomes [23]. If the YFV vaccine really protects against ZIKV infection and its outcomes, there is a vaccination model that is safe, fast, and cheap, and whose safety is already well known [21,23]. In the present study, we ascertained the presence and titers of antibodies and outcomes in women who had a ZIKV infection during pregnancy and were followed up at a reference hospital for infectious diseases in the Brazilian Amazon, a region with massive immunization against YFV.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Taken together, these studies suggest that the yellow fever vaccine may be important in the prophylaxis of ZIKV infections and their outcomes [23]. If the YFV vaccine really protects against ZIKV infection and its outcomes, there is a vaccination model that is safe, fast, and cheap, and whose safety is already well known [21,23]. In the present study, we ascertained the presence and titers of antibodies and outcomes in women who had a ZIKV infection during pregnancy and were followed up at a reference hospital for infectious diseases in the Brazilian Amazon, a region with massive immunization against YFV.…”
Section: Introductionmentioning
confidence: 77%
“…In type I interferon receptor knockout mice (A129) and BALB/c and SV-129 immunocompetent mice (A129 background), vaccination against YFV provided protection against ZIKV, reduced mortality and cerebral viral load in all mice, and prevented blood loss and loss of weight in BALB/c mice [23]. An in vitro assay showed that ZIKV was capable of infecting BeWo cell lines (derived from human placenta and mimicking the structure and function of the syncytiotrophoblast layer) and HU-VEC (umbilical vein cells), and YFV antibodies presented an impact on ZIKV, depending on the type of cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards auditory assessment, only five children underwent the appropriate examination and one presented with alterations in the left ear. In children with microcephaly, the prevalence of hearing loss was 6.6% 23 . No child had a more specialized ophthalmological evaluation performed, such as fundoscopy, which prevents us from commenting on important limitations in vision.…”
Section: Discussionmentioning
confidence: 99%